The recognition of the ancillary authority of the FCC by the US Supreme Court: convergence with the application of the theory of implicit powers in Brazilian law - David Sebastian (GoAcademica Research & Publishing, 2023)
This report compares the institutes of ancillary authority and implicit powers in the development of theory on administrative competences of Brazilian regulatory agencies. The delineation of the ancillary competence of the FCC was described based on judgments of the Supreme Court of the United States and the Court of Appeals for the District of Columbia. Doctrinal lessons and manifestations of Ministers of the Brazilian Federal Supreme Court were presented on the recognition of implicit powers to the necessary fulfillment of legal duties. Results – The confluence of these two theoretical approaches for the recognition of competences not directly expressed by regulatory agencies was demonstrated. The work contributes to the recognition of competences of the Brazilian telecommunications regulatory agency which, although not expressly provided, emerge as an imperative for the fulfillment of responsibilities directly given by law to that autarchy. The article presents a current legal institute in the North American tradition whose application to the Brazilian telecommunications area has not yet been established, despite its compatibility with concepts already accepted in Brazilian law.